The Effectiveness of Project-Based Learning Compared to Conventional Methods in Teaching Applied Mathematics for Ship Stability and Center of Mass Calculation - Yudhiyono, Yudhiyono; Y. A Nalle, Carles (Journal La Edusci, 2025)
Mathematics constitutes a vital foundation in maritime education, serving as an essential tool for ensuring safety, operational efficiency, and sustainability in the shipping industry. Its applications extend to critical areas such as route optimization, cost reduction, and environmental protection. Nevertheless, applied mathematics is often perceived as one of the most challenging subjects for nautical students, largely because of the difficulty in linking abstract concepts to practical, real-world maritime problems. This learning gap highlights the need for pedagogical strategies that can transform theoretical knowledge into tangible applications relevant to the maritime field. Project-Based Learning (PBL) has emerged as an effective instructional approach to address these challenges by promoting active learning, enhancing problem-solving abilities, and fostering both creativity and critical thinking. In maritime education, PBL can be particularly impactful in teaching complex topics such as ship stability, where mathematical principles play a central role. Ship stability, especially in relation to intact conditions, is crucial in vessel design and operation, as it determines a ship’s capacity to resist external forces and recover equilibrium. A key mathematical component of this process is the calculation of a vessel’s center of mass, which integrates mass distribution across structural components and loading conditions. By constructing ship models and applying coordinate-based methods, students can connect theoretical mathematics with practical stability analysis. This experiential approach not only deepens conceptual understanding but also equips future maritime professionals with the analytical competencies essential for safe and efficient operations in the global shipping environment.